Correlation among Antioxidant, Antimicrobial, Hemolytic, and Antiproliferative Properties of Leiothrix spiralis Leaves Extract - de Freitas Araujo, Marcelo Gonzaga [UNESP]; Hilario, Felipe [UNESP]; Vilegas, Wagner [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Sotomayor, Claudia Elena; Bauab, Tais Maria [UNESP] (Mdpi Ag, 2012)
The biological activities of a plant extract depend on a complex sum of individual properties including the antioxidant activity. Several biological activities protect against the harmful action of reactive oxygen species (ROS), and here we focused our attention on the relationship between the biological activities tested and the antioxidant properties. In this study, the total flavonoid content as well as the antioxidant, antimicrobial, hemolytic and cytotoxicity activities of the methanolic extract of Leitothrix spiralis leaves were evaluated. The extract showed a total flavonoid content of 19.26% and the chemical characterization by HPLC-PAD confirmed the presence of flavonoids as the major secondary metabolite compounds. Significant antioxidant activity (IC50 = 1.743 mu g/mL +/- 0.063) was demonstrated and was effective against Gram-negative organisms and all Candida strains tested, and showed an ability to inhibit hyphal formation. Non-hemolytic and antiproliferative activity could be demonstrated.
Keywords: Leiothrix spiralis; luteolin; antioxidant; antimicrobial; hemolytic; citotoxicity